2020
DOI: 10.20289/zfdergi.637793
|View full text |Cite
|
Sign up to set email alerts
|

Polen Kaynağı Olarak Kokulu Gül Genotipleri İle Yapılan Tozlama Tohum Oluşumunu Etkiler Mi?

Abstract: Does pollination with scented Rose genotypes as pollen source affect seed setting? ÖZ Amaç: Gül ıslahında ebeveyn seçimi başarıyı etkileyen faktörler arasında yer alır. Ebeveyn seçimi ve kombinasyonların belirlenmesinde ıslahçının; ploidi seviyesi, ebeveynlerin verimliliği, polen canlılığı, meyve başına tohum sayısı ve tohumların çimlenme oranı gibi faktörleri dikkate alması başarı oranını etkilemektedir. Bu çalışma, tozlamada polen kaynağı olarak kullanılan kokulu ve kokusuz gül genotiplerinin meyve tutum ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Cross-incompatibility and disparities at the ploidy level could cause low hip-set percentages in most tetraploid roses. In this regard, the present study is consistent with the findings of other researchers ( Morey, 1959 ; Rajapakse et al., 2001 ; Kazaz et al., 2020 ; Dogan et al., 2022 ). Fagerlind (1954) reported that, although the union of gametes from both parents could occur, not all hybrids might necessarily have a good seed set or viable embryos.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Cross-incompatibility and disparities at the ploidy level could cause low hip-set percentages in most tetraploid roses. In this regard, the present study is consistent with the findings of other researchers ( Morey, 1959 ; Rajapakse et al., 2001 ; Kazaz et al., 2020 ; Dogan et al., 2022 ). Fagerlind (1954) reported that, although the union of gametes from both parents could occur, not all hybrids might necessarily have a good seed set or viable embryos.…”
Section: Discussionsupporting
confidence: 94%
“…On the other hand, Datta (2018) stated that the fertility of miniature roses is high when used as pollen parents, and a good fruit formation, the number of seeds per fruit, and the germination rate can be obtained when hybridized with climbers, floribundas, or shrub roses. In addition, although many researchers reported that the difference in the number of seeds per fruit was due to different pollen viability and germination rates of the parents, it was reported that wild and old garden roses had a higher pollen quality than hybrid roses, which increased fruit formation and the number of seeds per fruit ( Ueda and Hirata, 1989 ; Gudin et al., 1991 ; Zlesak et al., 2007 ; Kazaz et al., 2020 ). Love et al.…”
Section: Discussionmentioning
confidence: 99%
“…Pitaya flowers open at 8: 00 pm, and they can remain open until the early hours of the morning. Pollen viability is very important for hybridization (Kazaz et al, 2020). Furthermore, intraspecific and interspecific hybridization also affect pollination.…”
Section: Introductionmentioning
confidence: 99%